Exploring Ideological Discourse Structures In English And Persian Translator Education - Khoshsaligheh, Masood (2012)
The present research in two phases investigated how students of English translation in Iranian universities tended to approach the source text with socio-political content critically for representations of embedded ideologies during English to Persian translation. The first phase was a quantitative study involving a self-designed questionnaire instrument and a purposive sample population of 469 participants. The second phase was a mixed-methods design study using think aloud protocol data from a criterion sample population of 10 participants.